Parallel calculation of differential quadrature method for the burgers-huxley equation - Ng, Su Ling, 1986-; Yeak, Su Hoe, Supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Matematik Kejuruteraan)) - Universiti Teknologi Malaysia, 2010